2006
DOI: 10.1124/mol.105.018622
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Inducers of Rodent GlutathioneS-Transferases Down-Regulate HumanGSTA1Transcription through a Mechanism Involving Variant Hepatic Nuclear Factor 1-C

Abstract: The regulation of human GSTA1 by chemical inducers of rodent glutathione S-transferases (GSTs) and the regulatory role of hepatic nuclear factor (HNF) 1 was investigated in Caco-2 cells. Treatment of preconfluent and confluent cells with 12-O-tetradecanoyl phorbol-13-acetate (TPA), 3-methylcholanthrene (3-MC), 2-tert-butyl-4-hydroxy-anisol (BHA), and phenobarbital (PB) reduced GSTA1 mRNA levels in preconfluent and confluent cells. Constitutive levels of GSTA1 and HNF1␣ mRNA were elevated 6.25-and 50-fold, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…Thus, to test this hypothesis we first verified that overexpression of vHNF-1C has a repressive effect on GSTA1 transactivation. Moreover, in a previous study we showed that vHNF-1C mRNA levels were high in preconfluent Caco-2 cells (and markedly higher than HNF-1␣) but comparatively lower in postconfluent cells (Romero et al, 2006). This finding may partially explain the differences observed in GSTA1 expression in pre-and postconfluent cells.…”
Section: Hnf-1c Mediates Repression Of Gsta1 By Il-1␤mentioning
confidence: 43%
See 2 more Smart Citations
“…Thus, to test this hypothesis we first verified that overexpression of vHNF-1C has a repressive effect on GSTA1 transactivation. Moreover, in a previous study we showed that vHNF-1C mRNA levels were high in preconfluent Caco-2 cells (and markedly higher than HNF-1␣) but comparatively lower in postconfluent cells (Romero et al, 2006). This finding may partially explain the differences observed in GSTA1 expression in pre-and postconfluent cells.…”
Section: Hnf-1c Mediates Repression Of Gsta1 By Il-1␤mentioning
confidence: 43%
“…Experiments were repeated twice with similar results. dent GSTs occurs via a mechanism involving enhanced binding vHNF-1C to the HRE in the GSTA1 promoter (Romero et al, 2006). Taken together, these data indicate an important regulatory role for HNF-1 in GSTA1 gene regulation; however, treatment conditions may determine whether HNF-1 has repressive or transactivating function based on the differential induction and dimerization of the various isoforms of HNF-1␣ and vHNF-1.…”
Section: Hnf-1c Mediates Repression Of Gsta1 By Il-1␤mentioning
confidence: 66%
See 1 more Smart Citation
“…The HNF1B isoforms are known to exhibit differences in function and target specificities; Isoforms (A) and (B) are transcriptional activators whereas isoform HNF1B(C) is a transcriptional repressor [35]. HNF1B isoforms have also been reported to activate different targets, for example, the HNF1B(C) isoform specifically has been demonstrated to negatively regulate the Glutahione-S-transferase A ( GSTA ) promoter, via a mechanism that involves Il-1beta [36]. Given the difference in the transcriptional properties and target specificity of these isoforms, we predict that the alterations to HNF1B profile we note may manifest as an alteration to the overall activity of the HNF1B gene and/or activation of a variant set of its target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Because TFs are potential targets of new anticancer drugs (Darnell Jr., 2002), we screened for the TFs that control expression of the GSTA1 gene and for their binding sites in the GSTA1 promoter. This analysis yielded identification of the 4 TFs including Sp1 (Ebert et al, 2003), AP-1 (Romero et al, 2006), c-Jun (Hayes and McMahon, 2001), and c-Fos (Tang et al, 2008) and of their binding sites in the GSTA1 promoter. The differential expression in GSTA1 genotypes defined by the C-69T substitution has been attributed to an alteration of the Sp1 transcription factor (Tijhuis et al, 2005).…”
Section: Discussionmentioning
confidence: 99%